Development of optimization technologies for building HVAC systems - Lu, Lu. (2008)
Development of optimization technologies for building heating, ventilating, and air conditioning (HVAC) systems, which consists of five heat transfer loops: indoor air loops, chilled water loops, refrigerant loops, condenser water loops, and outdoor air loops.